Analysis of sustainable tourism management in the Huta Tinggi tourism village - Kairi, Nur Khafizha; Andri, Delvi; Siregar, Ridha Nabila (Journal of Commerce, Management, and Tourism Studies, 2023)
Huta Tinggi Tourism Village has an interesting potential to visit. This village overlooks Samosir island, North Sumatra, which has natural beauty. Huta Tinggi tourism village is surrounded by stunning natural beauty. You can enjoy views of the green and lush hills, vast expanses of rice fields, and the river that flows around the village. In addition, the Batak culture is rich in cultural performances, tourists can explore and experience the uniqueness of Batak culture, including traditional dance, music and culinary delights. You can also visit traditional Batak houses and interact with local residents to understand more about their lives. Arts and crafts of Huta Tinggi tourism village is also known for its unique arts and crafts. The village is also known-well as agrotourism and ecotourism objects.